Preparation and structure evaluation of new derivatives of polyvalent iodine(III) based on 2-iodophenylbenzoimidazole; Современные проблемы органической химии - Vlasenko Yu. A. Yuliya Aleksandrovna (2017, 2017)
Заглавие с экрана